Introducing a Common University Entrance Test in India - Nandi, Emon (International Higher Education, 2022)
The National Education Policy 2020 advocated radical reforms in Indian higher education. Introducing a Common University Entrance Test in central universities is one such measure, expected to save students’ time, energy, and costs and tackle the issue of steep cut-offs in colleges and universities. But it may lead to a proliferation of coaching companies, limiting access for students from vulnerable backgrounds. It may also limit universities’ autonomy in selecting students, and erode diversity.